An information-processing model of bandwagon effects on media users’ movie viewing selections - Xu, Xuexin (2015)
This dissertation studies bandwagon effects on media users’ selections of content products and the antecedent to this effect. Building on the economic theory of information cascade and the psycho-cognitive theories on information processing, this study postulates that when facing a wide-ranging variety of media content offerings, people tend to make choices in or through ways that are sensitive to how others have reacted to those offerings. This inclination gives rise to bandwagon effects—the media users tend to gravitate toward those objects that have been known as popular. Furthermore, an antecedent to the bandwagon effect is how uncertain the recipients feel about the value, quality, or relevancy of the media content. Accordingly, this dissertation also inspects the role of informational uncertainty in stimulating the strength of bandwagon effects in the context of “movie audience” in particular. This dissertation comprises a comprehensive analysis of real-market data and a laboratory experiment. The data analysis empirically examined the bandwagon effect on foreign audiences’ viewing choices of Hollywood movies at the aggregate level. Regression analysis was conducted using the data of Hollywood movies’ box office revenues in 73 countries during the 2003 – 2007 periods. The results confirmed the aggregate bandwagon effect in audiences’ selections of Hollywood movies and showed that the strength of the bandwagon effect is magnified by how uncertain people are about the quality of movies, measured by the amount of movie information that audiences are confronted with and their level of unfamiliarity with the cultural background of Hollywood movies. The experiment, on the other hand, was carried out to study bandwagon effects at the individual level by examining user responses to movies shown on a Website. In particular, this study examined qualitative versus quantitative bandwagon effects associated with systematic versus heuristic information-processing modes. The Process Dissociation Procedure (PDP) was utilized to reveal the independent contributions of the two types of bandwagon behaviors to audiences’ content-selection decisions. This study further examines the influences of factors with respect to quality uncertainty on the magnitudes of the two types of bandwagon effects. The results showed that cognitive load is significantly associated with the strength of qualitative and quantitative bandwagon effects. An increase in the familiarity with Hollywood movies leads to a decrease in the quantitative bandwagon effect. Furthermore, an increase in the need for cognition would lead to an increase in the strength of qualitative bandwagon effect when participants are confronted with a high cognitive load. Taken together, these studies shed light on the overarching thesis of how humans make content selections under the circumstances of informational uncertainty. The dissertation seeks to make both theoretical and methodological contributions to the understanding about people’s social reactions to choices and tendency for choice imitation, which is still incomplete.